Regulating the Direction of Innovation - Gans, Joshua (National Bureau of Economic Research, 2024)
This paper examines the regulation of technological innovation direction under uncertainty about potential harms. We develop a model with two competing technological paths and analyze various regulatory interventions. Our findings show that market forces tend to inefficiently concentrate research on leading paths. We demonstrate that ex post regulatory instruments, particularly liability regimes, outperform ex ante restrictions in most scenarios. The optimal regulatory approach depends critically on the magnitude of potential harm relative to technological benefits. Our analysis reveals subtle insurance motives in resource allocation across research paths, challenging common intuitions about diversification. These insights have important implications for regulating emerging technologies like artificial intelligence, suggesting the need for flexible, adaptive regulatory frameworks
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Technologiepolitik; Innovation; Regulierung; Externer Effekt; Entscheidung unter Unsicherheit; Zeit; Allokation; Diversifikation; Theorie; Economics of Regulation; Technological Change: Choices and Consequences; Diffusion Processes